Draft Code of Ethics - Media, Arts and Entertainment Alliance and Media, Arts and Entertainment Alliance, (Pacific Journalism Review : Te Koakoa, 1996)
This is the recomended revised Journalist Code of Ethics drafted by Australia's Media, Arts and Entertainment Alliance (MEAA):
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYzaTIuNTc5